Thinking-language Disorders Types’ of Schizophrenia Spectrum Disorders Patients - E.M. Smerchinskaya; I.A. Tregubenko; E.R. Isaeva (Клиническая и специальная психология)
In the study of schizophrenia, special attention is paid to speech disorders. However, the descriptions of linguistic component are usually phenomenological. An objective structure analysis of language is needed, which could be useful to identify additional markers in assessing mental state and clarify criteria for differential psychodiagnostic. The possibility of adapting existing English-language studies is ambiguous, and a method based on the Russian-language sample is required. The study is aimed to identify types of speech characteristics in patients with schizophrenic spectrum disorders related to patopsychological thinking characteristics. The sample consisted of 70 people: 45 schizophrenia patients, 25 conditionally healthy participants. Methods used: expert assessment, experimental methods (tests of thinking, analysis of speech production), content-analysis, statistical analysis. Schizophrenia patients’ oral and written speech consist of less words, descriptions of feelings and thoughts than healthy participants. Schizophrenia patients’ speech is grammatically simpler, more formal, more inclusive, low communicative than healthy participants speech. Three types of written speech were found in patients with schizophrenia: Peculiar description of internal experiences, Narrative poverty, Reference to “I”. Two types of oral speech were also found: Narrative poverty, "Philosophizing". All types of written speech and Philosophizing in oral speech were significantly related to thinking disorders. The 5 speech characteristics that form in connection with thinking disorders characteristic of schizophrenia result in 3 types of speech-thinking disorders.